(untitled) (Ameghiniana, 2013)
Resumen. Por primera vez se describe e ilustra el hallazgo de un ejemplar de Paraconularia sp. con su ápiceunido al cirro de un crinoideo. La disposición de los organismos sugiere que el conulárido estuvo originariamente fijo al crinoideo. El material estudiado proviene del Puesto La Carlota (Provincia del Chubut, Argentina) y pertenece a la Zona de Callitomaria tepuelensis-Streblochondria sp. (Pérmico temprano). Abstract. NEW EVIDENCE ABOUT THE MODE OF LIFE OF CONULARIIDA. The occurrence of one specimen of Paraconularia sp. with the apex connected to a crinoid cirrus is described and figured for the first time. This disposition suggests that the conulariid had a primary, apical attachment to the crinoid. The material comes from Puesto La Carlota (Chubut Province, Argentina) and belongs to the Callitomaria tepuelensis- Streblochondria sp. Zone (Early Permian).